Membaca Percakapan Konseling Antenatal Care: Wawancara Eksploratif Dengan Ibu Hamil - Ardhini Reswari; Nuryanti Nuryanti; Agoeng Noegroho (UNIVED PRESS, Universitas Dehasen Bengkulu, 2026)
This research assumes that conversation quality in Antenatal Care (ANC) counseling determines whether clinical messages stay as knowledge or become daily behavior. It maps how pregnant women interpret message content, delivery, and closure so that recommendations feel relevant and actionable at home. A qualitative design used semi-structured face-to-face interviews with three pregnant women who received ANC counseling in the last three months. The interview guide combined key ANC message themes, Communication Accommodation Theory (CAT), and the Health Belief Model (HBM). Data were audio-recorded, transcribed verbatim, member-checked, and analyzed using reflexive thematic analysis. Findings show that mothers recall core advice on nutritious eating, light activity, and clinic visits, but operational details such as concrete portions, how to take iron tablets, and prioritized danger signs are not consistently conveyed. Counselors generally use everyday language and a comfortable pace, but message structure is uneven across topics. Home follow-up uses simple cues such as alarms, notes in the maternal and child health book, and family members who act as natural reminders. The study concludes that counseling effectiveness depends on content completeness and how conversations are structured and closed, and recommends a four-step micro-SOP with teach-back closure so ANC messages are understood, remembered, and practiced.